HUNIAN PRASEJARAH GUA KARAS KAIMANA - Hari Suroto (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
Excavations conducted at the site Gua Karas managed to open three boxes in sector I, the box GKQI (I6) dig as deep as 150 cm, box GKQI (F5) dig as deep as 130 cm, box GKQI (F6) dig as deep as 120 cm. This excavation produced findings are quite varied material culture that fragments of ceramic, pottery fragments, metal fragments, human bones, the remains of food in the form of shells of marine molluscs, freshwater mollusc shells, bone, various types of fauna, plant seeds, and charcoal combustion. Utilization Karas cave as a place to live based on the natural resources available in the vicinity, also based on the comfort and safety Cave Karas from natural disturbances. Utilization Cave Karas intensively marked by numerous archeologicalfindings in the form of everyday equipment (artifacts) andfood waste (ekofak) in the thick cultural layers. The findings demonstrate the use of multi-function varies Cave Karas, besides shelter also serves as the burial. Man Cave Karas cultural support in the past depends on the natural resources around. Based on the findings of leftovers in the form of marine mollusc shells and fish bones, indicating human cruising supporting Karas Caves in getting food source to reach the coast. Besides supporting man cave karas also made contact with the outside, this is evidenced by the findings of fragments of iron, ceramics and pottery.